2012
DOI: 10.4414/smw.2012.13551
|View full text |Cite
|
Sign up to set email alerts
|

Perception of non-invasive ventilation in adult Swiss intensive care units

Abstract: The real utilisation scenario of non-invasive ventilation (NIV) in Swiss ICUs has never been reported. Using a survey methodology, we developed a questionnaire sent to the directors of the 79 adult ICUs to identify the perceived pattern of NIV utilisation. We obtained a response rate of 62%. The overall utilisation rate for NIV was 26% of all mechanical ventilations, but we found significant differences in the utilisation rates among different linguistic areas, ranging from 20% in the German part to 48% in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
3
1
1
Order By: Relevance
“…The results have shown that financing is recognised worldwide as the most important factor responsible for NIV limitation in both acute and chronic respiratory failure in all economies, but the economic burden is highest in poorer countries ( tables 2 and 3 ) [ 5 ]. Our findings are not in agreement with previously published work indicating that lack of physician knowledge, insufficient respiratory therapist training and inadequate equipment are the most important factors limiting NIV use [ 6 , 7 ]. We have confirmed that medical doctors are still mainly involved in NIV provision, although respiratory therapists are well trained and may be cost-effective in comparison with employing medical doctors at the patient's bedside [ 8 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The results have shown that financing is recognised worldwide as the most important factor responsible for NIV limitation in both acute and chronic respiratory failure in all economies, but the economic burden is highest in poorer countries ( tables 2 and 3 ) [ 5 ]. Our findings are not in agreement with previously published work indicating that lack of physician knowledge, insufficient respiratory therapist training and inadequate equipment are the most important factors limiting NIV use [ 6 , 7 ]. We have confirmed that medical doctors are still mainly involved in NIV provision, although respiratory therapists are well trained and may be cost-effective in comparison with employing medical doctors at the patient's bedside [ 8 ].…”
Section: Discussioncontrasting
confidence: 99%
“…7 NIV is increasingly being used in many countries, but NIV use remains highly variable. It is used mainly for COPD exacerbations and CPE 89,90,[92][93][94] ; use for hypoxic respiratory failure and earlier extubation is still infrequent and mainly at specialized centers. 9 In Europe the rate of NIV use in ICUs is approximately 35% of ventilated patients, and 60% in respiratory ICUs and emergency departments.…”
Section: Real-life Applicationmentioning
confidence: 99%
“…A questionnaire developed in adult ICus in Switzerland found that overall utilization rate for noninvasive ventilation (nIv) was 26% of all mechanical ventilations, also showing that the preferred location of nIv initiation in the acute hospital was the ICu (86%), not the emergency department 31 . We showed that only one ICu did not implement this method.…”
Section: Discussionmentioning
confidence: 99%